2020
DOI: 10.1186/s13054-020-2790-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a national quality improvement program on ICUs in China: a controlled pre-post cohort study in 586 hospitals

Abstract: Introduction: Patient safety and critical care quality remain a challenging issue in the ICU. However, the effects of the national quality improvement (QI) program remain unknown in China. Methods: A national ICU QI program was implemented in a controlled cohort of 586 hospitals from 2016 to 2018. The effects of the QI program on critical care quality were comprehensively investigated. Main results: A total of 81,461,554 patients were enrolled in 586 hospitals, and 1,587,724 patients were admitted to the ICU o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…Therefore, we designed this study to investigate the relationship between structure indicators of ICU and C ssc in China. In our previous study, a multifaceted Q ICU intervention was effective in improving 3 and 6-h C ssc in septic shock in China [ 14 ]. In this study, we found that 6-h C ssc was lower than 3-h C ssc .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we designed this study to investigate the relationship between structure indicators of ICU and C ssc in China. In our previous study, a multifaceted Q ICU intervention was effective in improving 3 and 6-h C ssc in septic shock in China [ 14 ]. In this study, we found that 6-h C ssc was lower than 3-h C ssc .…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a nationwide retrospective cohort study using the surveillance data from the national quality improvement (QI) program in ICUs in China. The program was designed and led by China National Critical Care Quality Control Center (China-NCCQC), the official national department regulating ICU quality control in China [ 13 ]. The national ICU QI program is a hospital-based continuous QI initiative, with multifaceted intervention implemented in multicenter voluntarily.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen ICU quality control indicators are adopted in the program, based on the recommendations by the National Health Commission of the People’s Republic of China on April 10, 2015 [ 17 ]. The indicators were described as previously [ 13 ], and listed as follows: (1) three structural indicators including proportion of ICU patients out of all total inpatients, proportion of ICU bed occupancy out of the total inpatient bed occupancy, proportion of ICU patients with acute physiology, and chronic health evaluation (APACHE) II scores ≥ 15 out of all ICU patients; (2) four process indicators including 3-h Surviving Sepsis Campaign (SSC) bundle compliance rate, 6-h SSC bundle compliance rate, microbiology specimen collection before antibiotic therapy, DVT prophylaxis rate); (3) eight outcome indicators including unplanned endotracheal extubation rate, reintubation rate within 48 h, rate of unplanned transfer to ICU, ICU readmission rate within 48 h, VAP incidence rate, CRBSI incidence rate, catheter-associated urinary tract infection incidence rate, ICU mortality.…”
Section: Methodsmentioning
confidence: 99%
“…The QI factors of the ICU were evaluated according to the National Clinical Quality Control Indictors for Critical Care Medicine, which were o cially recommended for the assessment of ICU performance by the National Health Commission of the People's Republic of China in 2015 [14]. In this study, 10 related factors were analyzed, including 5 structural factors, 3 process factors and 2 outcome factors.…”
Section: Variable and Measurementsmentioning
confidence: 99%